Biplot analysis of seed priming effects on maize seedling growth traits - Čanak Petar; Mirosavljević Milan; Zorić Miroslav; Ćirić Mihajlo; Vujošević Bojana; Mitrović Bojan; Stanisavljević Dušan (Ratarstvo i Povrtarstvo, 2018)
The objectives of this study were to determine the effects of different priming treatments and genotypes on maize germination and early seedling growth traits, as well as to examine the associations among these traits. In addition, the application of genotype by trait biplot methodology in this type of analysis was evaluated. Seed priming treatment was conducted on ten maize inbred lines by soaking seeds in water (hydropriming) or in 0.5% KNO3 solution. Seed was sown in sterile moistened sand and placed at suboptimal (15°C) and optimal temperature (25°C) for seven days. After that, seedling length and seedling weight were measured, final germination, time to 50% emergence and vigour index were calculated. The results showed that seed priming can improve seedling growth traits at both temperatures. There are differences in genotype responses to various seed priming solutions. The observed differences represent useful information for the selection of adapted maize inbred line and adjustment of priming treatment for sowing in different temperature conditions. This study showed that biplot could easily be used for assessing the effect of seed priming, or some other treatment, on seedling growth traits. Moreover, it can be used to understand the associations among the seedling growth traits.